CYPERACEAE OF THAILAND (EXCL. CAREX) - JH Keen (Reinwardtia, 1961)
This is an enumeration of 174 examined spacies and of 11 not examined ones, in 16 genera, collected in or recorded from Thailand. The treatment is largely in the same way as in the 'Florae Siamensis Enume-ratio'. Synonyms and references are given. All examined specimens are listed for each of the 7 provinces of Thailand indicated on a map, and their field notes are recorded. Distribution outside Thailand is given in some detail, and occasionally nomenclatural or other notes are added. In Lepironia 1 species is recognized, in Mupaniu 5, in Hypolyf/ntm 1, in Fuirena 2, in Lipocarpha 2, in H&miearpha 1, in Scirpus 10, in Elco-charis 8, in Fimbristylis 51, in Bulbostylis 3, in Cyperus 53, in Rltyncho-spora 7, in Triocostularia 1, in Schoemis 'I, in Gahnia 1, in Scleria 23. Novelties are Fimbristylis grudlenta var. psilopodu, Scleria biflora ssp. fervuginea, (Ohwi), and Scleria retieuiata (Holtt.). An index to collectors' numbers is given at the end.